Ophthalmoscopic interpretation of fundic lesions in animals - Blanchard, Gary L.; American Animal Hospital Association; Pitman-Moore, Inc. (Washington Crossing, N.J. : Continuing Education Library, Pitman-Moore, 1981)
Fundamentals of indirect ophthalmoscopic examination are presented with discussion of normal and pathological findings.
Slides mounted in 1 carousel.
"A Pitman-Moore continuing educational program."
Produced in cooperation with the American Animal Hospital Association.
Keywords: Veterinary ophthalmology